2022
DOI: 10.3390/children9111735
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Clinical Profile of Pediatric Burns in the COVID-19 Era: The Experience of a Reference Center

Abstract: Pediatric burns represent a significant public health problem. We analyzed the characteristics of pediatric burns in a reference center, in order to identify better strategies for prevention and care. Burn patients admitted to the pediatric departments of our hospital from January 2020 to June 2022 were retrospectively evaluated. Age, gender, the etiology of injuries, the total burn surface area (TBSA), the degree of burns, the length of hospital stay (LOS), concomitant SARS-CoV-2 infection, and burn surface m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 30 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…There were no statistically significant differences observed among pediatric burn cases regarding sex. Our results were similar to an earlier study conducted in the USA and Italy [158,159]. Nevertheless, one study at Linköping University Hospital of Sweden reported that more males (70%) were burned cases than females [160].…”
Section: Discussionsupporting
confidence: 91%
“…There were no statistically significant differences observed among pediatric burn cases regarding sex. Our results were similar to an earlier study conducted in the USA and Italy [158,159]. Nevertheless, one study at Linköping University Hospital of Sweden reported that more males (70%) were burned cases than females [160].…”
Section: Discussionsupporting
confidence: 91%
“…This hospital had zero transmissions between COVID-19-positive patients and others, and treatment of the COVID-19 infection was not burdened by major sequelae. 67 During the stay-at-home order, they reported delayed presentation of greater than 24 hours in 19% of patients after injury, which they speculate to be attributed to initial fear of viral exposure at the hospital during the pandemic. 67 An Israeli dedicated pediatric tertiary care center reported a rise in pediatric burn cases and admissions, especially from domestic accidents, and time from injury to presentation in the emergency department was longer compared with pre-COVID.…”
Section: Burn Managementmentioning
confidence: 96%
“…67 During the stay-at-home order, they reported delayed presentation of greater than 24 hours in 19% of patients after injury, which they speculate to be attributed to initial fear of viral exposure at the hospital during the pandemic. 67 An Israeli dedicated pediatric tertiary care center reported a rise in pediatric burn cases and admissions, especially from domestic accidents, and time from injury to presentation in the emergency department was longer compared with pre-COVID. As a result of the increased admissions, they established a prehospital clinic to triage patients as those admitted to the hospital or those treated with telehealth.…”
Section: Burn Managementmentioning
confidence: 96%
See 2 more Smart Citations